1999
DOI: 10.1007/bf02784425
|View full text |Cite
|
Sign up to set email alerts
|

Zinc sulfate supplementation improves thyroid function in hypozincemic down children

Abstract: In subjects affected by trisomy 21 (Down syndrome), hypothyroidism is the most common endocrinological deficit. Plasma zinc levels, which are commonly detected below the normal range in Down patients, are related to some endocrinological and immunological functions; in fact, zinc deficiency has been shown to impair immune response and growth rate. Aims of this study were to evaluate (1) the role of zinc deficiency in subclinical hypothyroidism and (2) thyroid function changes in Down children cyclically supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 23 publications
1
25
0
5
Order By: Relevance
“…Furthermore, zinc supplementation improves thymic and immune functions in children with Down's syndrome. 9,10 Specifically, children with Down's syndrome and low zinc levels have a higher incidence of subclinical hypothyroidism and higher TSH levels that can be improved by zinc replacement. 10 In Turkey, legislation necessitating the iodization of table salt was started in 1999 by the addition of 50-70 mg/kg potassium iodide or 25-40 mg/kg potassium iodine in order to prevent endemic goitre caused by iodine deficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, zinc supplementation improves thymic and immune functions in children with Down's syndrome. 9,10 Specifically, children with Down's syndrome and low zinc levels have a higher incidence of subclinical hypothyroidism and higher TSH levels that can be improved by zinc replacement. 10 In Turkey, legislation necessitating the iodization of table salt was started in 1999 by the addition of 50-70 mg/kg potassium iodide or 25-40 mg/kg potassium iodine in order to prevent endemic goitre caused by iodine deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Specifically, children with Down's syndrome and low zinc levels have a higher incidence of subclinical hypothyroidism and higher TSH levels that can be improved by zinc replacement. 10 In Turkey, legislation necessitating the iodization of table salt was started in 1999 by the addition of 50-70 mg/kg potassium iodide or 25-40 mg/kg potassium iodine in order to prevent endemic goitre caused by iodine deficiency. In a recent study evaluating goitre prevalence in school age children in Ankara, it was shown that the iodine sufficiency was reached within 7 years of initiation of countrywide prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…This was explained as being a consequence of delayed maturation of the hypothalamic-pituitary-thyroid axis in children with DS, which might be the cause for isolated elevation of TSH levels in a large number of these patients. Other reasons for this transient elevation in TSH levels have been suggested by other studies, namely, low serum levels of zinc, 16,17 which is implicated in some endocrine and immunological processes; and low serum levels of selenium, which is found in proteins responsible for thyroid hormone synthesis. 18 In this study, no significant difference was observed between the means of initial TSH serum levels of patients who normalized their TSH levels and of those in whom these levels were persistently high during the reassessment.…”
Section: Resultsmentioning
confidence: 83%
“…7,10 Controversy exists over whether such elevation is a risk factor for impaired intellectual outcome in these children 11 and the cause for such elevation has not been clarified yet. [16][17][18][19] Culter et al 2 suggest that the isolated elevation of TSH levels in children with DS, even in the absence of thyroid peroxidase autoantibody (anti-TPO), might be an early sign of primary autoimmune hypothyroidism. Cases with positive anti-TPO are expected to have a frequent progression to overt thyroid disease.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc deficiency has been shown to impair immune response and growth rate (Bucci et al, 1999) whereas dietary zinc supplementation has been reported to transiently improve thymic function (Napolitano et al, 1990). Thyroxine treatment may improve development and growth of young DS children and has been proposed as a therapeutic tool to maximize the early development and growth in DS neonates (van Trotsenburg et al, 2005).…”
Section: Hormone Treatmentsmentioning
confidence: 97%